Influence of emergence delirium-related knowledge and nursing stress, practice, and confidence levels on the performance of recovery room nurses: A cross-sectional study. - Woo Jeong Ban; Jung Min Lee; Soo-Hyun Nam (PLoS ONE)
In this study, we aimed to explore the relationships between knowledge of emergence delirium (ED) and nursing stress, practice, confidence, and performance levels, as well as to identify factors influencing the performance of recovery room nurses. We conducted a cross-sectional study with 135 recovery room nurses at a general hospital in South Korea. The nurses completed a questionnaire from April 12 to April 25, 2023. Data were analyzed using multiple linear regression to examine factors associated with nursing performance in relation to ED. Nursing performance showed a significant negative correlation with nursing stress levels and a moderate positive correlation with nursing practice and confidence levels. Furthermore, ED education, nursing practice, and nursing confidence are factors influencing nursing performance. To enhance the performance of recovery room nurses in caring for patients with ED, we recommend developing a tailored educational program that focuses on increasing both the confidence levels and practical skills of nurses, thereby meeting the specific needs of the patients.